1998
DOI: 10.1111/j.1559-1816.1998.tb01352.x
|View full text |Cite
|
Sign up to set email alerts
|

The Black‐Sheep Effect: How Positive and Negative Advertisements Affect Voters' Perceptions of the Sponsor of the Advertisement1

Abstract: Participants read a positive or negative (mock) political advertisement that was sponsored by either an in‐group (subject and sponsor were members of the same political party) or an out‐group (subject and sponsor were members of different political parties) member. The results found support for a black‐sheep effect. An in‐group sponsor of a positive advertisement was evaluated more positively than any out‐group member, regardless of advertisement type, or an in‐group member who sponsored a negative advertiseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…The findings here are similarly mixed. Some research suggests that citizens support candidates who attack at lower levels (Shapiro and Rieger 1992;Weaver-Lariscy and Tinkham 1996;Matthew and Dietz-Uhler 1998;Lemert et al 1999;Min 2004;Brader 2005) whereas other research implies just the opposite: that citizens are less supportive of candidates who use negative messages (Roddy and Garramone 1988;Ansolabehere and Iyengar 1995;Kaid 1997;Shen and Wu 2002;King and McConnell 2003).…”
Section: Public Opinion and Campaign Negativitymentioning
confidence: 95%
“…The findings here are similarly mixed. Some research suggests that citizens support candidates who attack at lower levels (Shapiro and Rieger 1992;Weaver-Lariscy and Tinkham 1996;Matthew and Dietz-Uhler 1998;Lemert et al 1999;Min 2004;Brader 2005) whereas other research implies just the opposite: that citizens are less supportive of candidates who use negative messages (Roddy and Garramone 1988;Ansolabehere and Iyengar 1995;Kaid 1997;Shen and Wu 2002;King and McConnell 2003).…”
Section: Public Opinion and Campaign Negativitymentioning
confidence: 95%
“…Reversals, however, of in-group favoritism have been reported. When one seriously violates the group norms, several studies report that the in-group may assess this behavior even more harshly than it would that of a non-group member (Barry et al, 2006;Begue, 2001;Mathews and Dietz-Uhler, 1998).…”
Section: Participant Gendermentioning
confidence: 98%
“…This appears to stem from a desire to protect a positive group identity-and thus self-identity (Tajfel and Turner 1986)-from the negative behaviors of an in-group member. Matthews and Dietz-Uhler (1998) found this dynamic at work in negative advertising. In an experiment using mock political ads, they found that participants had more negative affective and behavioral reactions to ads alleging that the opponent ''did not support family values in his personal and professional life'' (Matthews andDietz-Uhler 1998, p. 1906) when the sponsor belonged to the same party as the participant.…”
Section: Advertising Tone and Targetmentioning
confidence: 95%
“…Matthews and Dietz-Uhler (1998) found this dynamic at work in negative advertising. In an experiment using mock political ads, they found that participants had more negative affective and behavioral reactions to ads alleging that the opponent ''did not support family values in his personal and professional life'' (Matthews andDietz-Uhler 1998, p. 1906) when the sponsor belonged to the same party as the participant. Matthews and Dietz-Uhler (1998) suggested that ''the backlash effect described by many researchers may be a manifestation of the black sheep effect' ' (p. 1905).…”
Section: Advertising Tone and Targetmentioning
confidence: 95%
See 1 more Smart Citation